Regulation of agricultural markets in Malawi - Duchoslav, Jan; Nyondo, Christone; Comstock, Andrew R.; Benson, Todd (International Food Policy Research Institute, 2022)
Agriculture holds special significance in Malawi, because most Malawian households depend primarily on this sector for income and food security. Therefore, legislation surrounding the agricultural sector, and the foundation it lays for the sector’s governance, are fundamental to the development prospects of the country. At their best, agricultural laws encourage farmers, traders (both domestic and international), and processors of agricultural commodities to fully engage and further invest in the agricultural sector. At their worst, they undermine confidence to do so.